The analysis of online communities as platforms for informational influences - Vus, Volodymyr; Albota, Solomiia; Dobrovolska, Viktoriya (My University, 2019)
The article deals with the basic definitions used to describe the communications of the Internet users. The classifications of the Internet community, which are based on the differences between the technical characteristics, structural organization, interface and the topics of the online communities, have been considered. The ways of discussion implementation for establishing communication between messages have been determined. In online communities, discussions have been implemented in two ways: linear (sequential) structure and tree-like (branch) structure. Given the ways in which discussion can be implemented, the relations between messages can be detected explicitly and implicitly. The online communities have the following means of transmitting information: messages, posts, likes, functions “share with”. Two types of informational activity – linguistic and signaling – have been regarded to classify these means. The communication of online community members via the information provided in the test form, used to convey verbal information, has been studied. In addition to verbal means of transmitting information in online communication, non-verbal and paraverbal means have been used. Non-verbal means used in online communities are emoticons and hyperlinks. Paraverbal means in online communities are represented by meta tags. The notion of discussion as a meaningful communication between messages has been defined. Discussions, as a dialogue structures, consist of alternate replicas of participants who take on the role of the sender and the recipient. The technologies of global search of relevant discussions in social Internet media have been considered. Using a meta-search system will increase the relevancy of output results and enable the creation of a "meta-net" of keywords, resulting in an increase in the number of searching results.
Keywords: online communities; information content; discussions; posts